New records to Brazil and Southern Hemisphere of corticolous and saxicolous lichens from the semiarid region in Ceará Stat - Cáceres, Marcela Eugenia da Silva; Mota Júnior, Narla; dos Santos, Lidiane Alves; Pereira, Thamires de Almeida; Aptroot, André (Iheringia, Série Botânica., 2017)
Lichens are an important element of the biodiversity of tropical regions, found in a variety of substrates. The Brazilian semiarid biodiversity is highly threatened due to land conversion for agricultural and cattle ranch. Until recently, only a few species had been reported from Ceará, the only State in Brazil covered almost entirely by Caatinga vegetation. The present work was carried out in Quixadá and Quixerá, in Ceará State, an area characterized by the presence of rock outcrops and inselbergs. As a result, 82 lichen species are here reported, from which 52 species are new records for Ceará, and 14 are reported for the fi rst time to Brazil. The great majority of species was saxicolous. This is the fi rst lichen inventory in this semiarid region of the state, and also the fi rst study to report a large number of saxicolous crustose microlichens in northeatern Brazil.